2020
DOI: 10.3389/fimmu.2020.01486
|View full text |Cite
|
Sign up to set email alerts
|

Repertoire Analysis of B-Cells Located in Striated Ducts of Salivary Glands of Patients With Sjögren's Syndrome

Abstract: A major complication of primary Sjögren's syndrome (pSS) is development of mucosa associated lymphoid tissue (MALT) B-cell lymphoma, particularly in salivary glands. These lymphomas express FcRL4 and are characteristically associated with lymphoepithelial lesions. Neoplastic B-cells may be derived from non-neoplastic glandular intraductal B-cells, also virtually all expressing FcRL4. A characteristic feature of MALT lymphomas is the production of rheumatoid factors (RFs), which are largely encoded by stereotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…How B cells are attracted into the epithelium is not fully understood, but the expression of CXCR3 probably has an important role, as intraepithelial B cells express CXCR3 and the salivary gland epithelium produces CXCL10 and other CXCR3 ligands upon activation 143 . These intraepithelial B cells, which are probably already activated before they migrate to the epithelium, can expand locally, as demonstrated by the high proportion of Ki67-staining cells and the expansion of clonal B cells within the striated ducts 169 , 170 . The latter finding suggests that additional activation and proliferation signals might be derived from epithelial cells, and possibly also from other intraepithelial immune cells, such as T cells and dendritic cells.…”
Section: Epithelial Cell–lymphocyte Crosstalkmentioning
confidence: 99%
See 1 more Smart Citation
“…How B cells are attracted into the epithelium is not fully understood, but the expression of CXCR3 probably has an important role, as intraepithelial B cells express CXCR3 and the salivary gland epithelium produces CXCL10 and other CXCR3 ligands upon activation 143 . These intraepithelial B cells, which are probably already activated before they migrate to the epithelium, can expand locally, as demonstrated by the high proportion of Ki67-staining cells and the expansion of clonal B cells within the striated ducts 169 , 170 . The latter finding suggests that additional activation and proliferation signals might be derived from epithelial cells, and possibly also from other intraepithelial immune cells, such as T cells and dendritic cells.…”
Section: Epithelial Cell–lymphocyte Crosstalkmentioning
confidence: 99%
“…Upregulation of CXCR3 and CD11c, and possibly also other integrins, on the B cell surface might have a role in keeping the cells within the epithelial layer. However, in addition to being present in ductal areas, B cell clones are also present, to some extent, in the periductal areas, suggesting that some cellular exchange occurs between these areas 170 .…”
Section: Epithelial Cell–lymphocyte Crosstalkmentioning
confidence: 99%
“…Given the increased proliferative activity, the potency of AID expression and their association with LEL, one could attribute to intraductal B cells characteristics capable of leading them to neoplastic evolution. Viser et al also demonstrated that most of the B cell clones found in their study did not express BCRs with homology for stereotypic RF sequences, a finding indicative of clonal expansion independent of a BCR with RF activity [81]. Thus they hypothesize that activated B cells migrate into the striated ducts in the SGs of patients with SS, irrespective of BCR specificity, while transformation to pathogenic RF expressing B cells is the result of lymphoma driver mutations acquisition, under the effect of the stimulatory environment of the striated duct [81,83].…”
Section: Fcrl4 Expressing B Cellsmentioning
confidence: 72%
“…Upregulation of genes associated with lymphomagenesis in FcRL4 + B cells has been recently shown, leading to the hypothesis that neoplastic MALT B-cells may arise from glandular FcRL4 + intraductal B cells [42]. Based on IGHV gene analysis Visser et al demonstrated the presence of B cell clones not only restricted to the ducts, but also seen in the periductal areas, indicating a possible translocation of clonal between the two compartments [81]. FcRL4 + B cells within the SGs of pSS patients can express activation-induced-deaminase (AID) [38,42,82].…”
Section: Fcrl4 Expressing B Cellsmentioning
confidence: 99%
“…In a very recent study of SjS patients it has also been shown a B cell clonal expansion in salivary gland of these subjects which they correlate to memory B cells. Although they observed a clonal expansion, they did not find either public clonotypes when analyzing the variable gene segment usage (65). In other autoimmune diseases such RA evidences have been found that indicate a B cell clonal expansion along with class-switching, SHM and autoreactivity, so the polyreactive expansion in SjS might be not that uncommon within autoimmune diseases (63).…”
Section: Discussionmentioning
confidence: 88%